Reduction in Heart Rate Variability in Autosomal Dominant Polycystic Kidney Disease - Silvia Lai; Marco Mangiulli; Adolfo M. Perrotta; Gianluca Di Lazzaro Giraldi; Massimo Testorio; Edoardo Rosato; Rosario Cianci; Antonietta Gigante (Karger Publishers, 2019)
Introduction: Cardiovascular disease is one of the main causes of morbidity and mortality in patients with autosomal dominant polycystic kidney disease (ADPKD). Autonomic dysfunction is associated with an increased risk for all cardiovascular events in the general population and can be evaluated with heart rate variability (HRV). Objective: To evaluate HRV in ADPKD patients with mild hypertension versus hypertensive patients with organ damage and healthy controls (HC). Materials and Methods: We have enrolled 65 patients: 21 ADPKD patients (10 males), 20 patients with hypertension (14 males), and 24 HC (10 males). Biochemical analysis, clinical evaluation, anthropometric data, intima-media thickness, 24-h ECG Holter recording, and echocardiography were investigated at the time of enrollment. Results: No significant differences in HRV parameters were found between ADPKD with mild hypertension and hypertensive patients with organ damage. The median of HRV variables in time domain as SDNN (global autonomic activity) was significantly lower in ADPKD and hypertensive patients than HC (p < 0.05). In the frequency domain analysis, low frequency (LF), which mainly reflects the sympathetic component, showed higher values in ADPKD and hypertensive patients than HC during the night (p < 0.01). During the night, the sympathovagal balance, LF/high frequency (HF), showed higher values in ADPKD and hypertensive patients than HC (p < 0.0001). Conversely, LF day was lower in ADPKD and hypertensive patients than HC (p < 0.01). HF, which mainly reflects the parasympathetic component, was lower in ADPKD and hypertensive patients during the night than HC (p < 0.0001). Conclusions: HRV reduction is present in ADPKD patients with mild hypertension in the absence of organ damage. The evaluation of sympathovagal balance can provide novel information on the cardiovascular risk in ADPKD patients in addition to classical risk factors.